Marketing Strategy for Mitraguna Online Financing Products in Increasing the Number of Customers - Hasibuan, Kiki Andrea Putri; Nasution, M. Lathief Ilhamy; Syakir, Ahmad (Graduate Program Magister Manajemen Pendidikan, 2024)
This study aims to determine potential marketing strategies to increase the number of customers in the online mitraguna financing product of Bank Syariah Indonesia, Kisaran sub-branch office. This research uses qualitative research methodology. In qualitative research, the findings are analyzed and then reported by the researcher. In this study, two different types of data were used, namely primary and secondary. Interviews were used to obtain primary data, while publications from relevant financial institutions as well as relevant scientific literature were used to collect secondary data. The results of the data analysis resulted in the largest threat weight of 0.092538, the largest opportunity weight of 0.571429, the highest weakness weight of 0.210526, and the highest strength weight of 0.421053. The average overall score of the Internal Factor Evaluation matrix is 2.736842, but the average score of the External Factor Evaluation matrix is 2.952381. The results of this study indicate that the marketing strategy that needs to be implemented lies in quadrant V, namely the strategy of maintaining and maintaining by obtaining 5 alternative strategies that are expected to contribute to the Bank Syariah Indonesia Kisaran sub-branch office to increase the number of online mitraguna financing customers.